2023
DOI: 10.1002/adfm.202209122
|View full text |Cite
|
Sign up to set email alerts
|

Designing Highly Conductive Sodium‐Based Metal Hydride Nanocomposites: Interplay between Hydride and Oxide Properties

Abstract: Sodium‐based complex hydrides have recently gained interest as electrolytes for all‐solid‐state batteries due to their light weight and high electrochemical stability. Although their room temperature conductivities are not sufficiently high for battery application, nanocomposite formation with metal oxides has emerged as a promising approach to enhance the ionic conductivity of complex hydrides. This enhancement is generally attributed to the formation of a space charge layer at the hydride‐oxide interface. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 103 publications
1
11
0
Order By: Relevance
“…Meanwhile, the interaction effect between conductors and insulating additives, such as oxides and polymers, which enhances the ionic migration due to the formation of active interfaces and the creation of fresh ionic environment, has been often reported for solid-state electrolytes. 12,13,24,25 In the present study, the strong interaction between Mg(BH 4 ) 2 Á1.9NH 3 and MgBr 2 Á2NH 3 evidenced by expansion in the lattice spacing of MgBr 2 Á2NH 3 (Fig. 1c and Fig.…”
supporting
confidence: 59%
“…Meanwhile, the interaction effect between conductors and insulating additives, such as oxides and polymers, which enhances the ionic migration due to the formation of active interfaces and the creation of fresh ionic environment, has been often reported for solid-state electrolytes. 12,13,24,25 In the present study, the strong interaction between Mg(BH 4 ) 2 Á1.9NH 3 and MgBr 2 Á2NH 3 evidenced by expansion in the lattice spacing of MgBr 2 Á2NH 3 (Fig. 1c and Fig.…”
supporting
confidence: 59%
“…These second phases were incorporated through the ball-milling method or the melt infiltration process; in other words, two phases were mixed using a physical approach. Ngene et al [13] revealed that this second-phase strategy could be attributed to the surface interaction between the oxides (Al 2 O 3 and SiO 2 ) and NaBH 4 . To strengthen the two-phase interface, the Na 2 B 12 H 12 phase was generated in situ through a gas-solid chemical reaction between NaBH 4 and B 2 H 6 .…”
Section: Introductionmentioning
confidence: 99%
“…As an inexpensive industrial reducing agent, the significant cost advantage of NaBH 4 has inspired interest in improving its Na + conductivity. The most straightforward way to improve conductivity is using a second‐phase incorporation strategy, such as NaBH 4 ‐C 60 , [ 12 ] NaBH 4 ‐Al 2 O 3 , [ 13 ] or NaBH 4 ‐SiO 2 . [ 13 ] The NaBH 4 ‐C 60 nanocomposite has shown an increase of four orders of magnitude in ionic conductivity compared with pure NaBH 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations